A Stable Focal Cerebral Ischemia Injury Model in Adult Mice: Assessment Using 7T MR Imaging - Zhang, F.; Guo, R.-M.; Yang, M.; Wen, X.-H.; Shen, J. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: A stable stroke experimental model is highly desirable for performing longitudinal studies using MR imaging. The purpose of this study is to establish a stable focal cerebral ischemia model with a high survival rate in adult mice. MATERIALS AND METHODS: One hundred twenty adult mice were randomly divided into 10 groups of 12 each to respectively undergo intraluminal suture occlusion, with suture insertion depths from 0.8 cm to maximum; thromboembolic occlusion; and hypoxic-ischemic injury with hypoxia exposure times from 30–120 minutes. Coronal brain T2-weighted images were obtained on a 7T scanner. The induced infarct volume and location were assessed and correlated with histologic TTC staining. One-day and 7-day survival rates were recorded. RESULTS: The infarct location was highly variable in the thromboembolic model, while it showed a cortex predominance in the intraluminal model with the suture insertion depth ≥1.4 cm, and the HI model with hypoxia exposure times ≥60 minutes (P = .001). The infarct volume in the intraluminal model with suture depths ≥1.4 cm (29.7 ± 3.3%, 35.4 ± 4.3%) and the HI model with the hypoxia exposure times ≥90 minutes (26.3 ± 4.1%, 33.4 ± 2.8%) were larger than other groups (9.7 ± 3.3%–20.9 ± 9.3%; P < .05). The HI group (72.5%) had higher 7-day survival rate than the intraluminal suture occlusion (28%) and thromboembolic occlusion groups (20%; P = .001). CONCLUSIONS: The HI injury model with a reproducible ishemia and high survival rate can be used for a longitudinal study of brain ischemia in adult mice. CCAcommon carotid arteryECAexternal carotid arteryHIhypoxia-ischemiaMCAOmiddle cerebral artery occlusionPBSphosphate buffered salinePPApterygopalatine arteryTTC2, 3, 5-triphenyltetrazolium chloride staining